A Qualitative Study Exploring Management of Food Intake in the United Kingdom During the Coronavirus Pandemic - Randall, Tennessee; Mellor, Chloe; Wilkinson, Laura L. (Frontiers in Psychology, 2022)
The coronavirus pandemic has impacted dietary quality through increased emotional eating and extended time spent at home, as well as instances of panic buying due to uncertainty over food availability. 40 participants (Female = 25; Mean age = 41.9 years (SD = 14.4) were interviewed about impacts of the lockdown on their eating habits. Identified themes from reflexive thematic analysis highlighted effective organization was vital to managing food purchases and consumption due to a reduced shopping frequency. However, overconsumption frequently occurred due to boredom and ease of accessing energy dense foods, which had negative implications for weight and body image After indulging, participants attempted to revert to prior eating habits and adhere to a nutritious diet. Many also expressed the importance of having enough food to feed families, which was often reported as a reason for buying extra supplies. Understanding the long-term impacts of changes to eating habits that account for the novel coronavirus context is required to preserve health and prevent unintended changes to weight.